2019
DOI: 10.1111/rda.13487
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a portable device (iSperm®) for the assessment of stallion sperm motility and concentration

Abstract: The objective of this study was to evaluate the accuracy of a novel, portable device (iSperm® Equine for assessing concentration and motility of stallion semen). In the first experiment, semen concentration was determined by the iSperm® Equine (Aidmics Biotechnology), Androvision® (Minitube) and NucleoCounter® SP‐100™ (ChemoMetec). The total motility and progressive motility were determined by the iSperm® Equine and the Androvision® using the manufacturer's guidelines. Frozen/thawed semen samples (n = 33) at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…However, similar to our findings, Dini et al (2019) showed high correlations between the iSperm and Nucleocounter SP-100 when measuring semen concentrations in samples on the lower side of the iSperm indicated range. Just as our results identified a strong correlation between CASA and iSperm for the measurement of progressive motility, Dini et al (2019) similarly reported a strong positive correlation between iSperm and Androvision. This demonstrates the utility and accuracy of the iSperm for the portable measurement of progressive motility for different species.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, similar to our findings, Dini et al (2019) showed high correlations between the iSperm and Nucleocounter SP-100 when measuring semen concentrations in samples on the lower side of the iSperm indicated range. Just as our results identified a strong correlation between CASA and iSperm for the measurement of progressive motility, Dini et al (2019) similarly reported a strong positive correlation between iSperm and Androvision. This demonstrates the utility and accuracy of the iSperm for the portable measurement of progressive motility for different species.…”
Section: Discussionsupporting
confidence: 91%
“… Dini and colleagues (2019) determined the iSperm for horses had different results on the ability of iSperm for the concentration of a semen sample ( Dini et al, 2019 ). They reported a higher correlation between the iSperm and the Nucleocounter SP-100 and less than 10% difference when measuring semen samples between 20 and 100 M/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm kinetic characteristics, including percentages of total motility (TM) and progressive motility (PM), straightline velocity (VSL, μm/s), mean curvilinear velocity (VCL, μm/s), and average path velocity (VAP, μm/s) were analyzed by iSperm  (version 4.5.2; Aidmics Biotechnology Co., LTD, Taiwan) software in fresh and cooled semen, as previously reported (Dini et al, 2019).…”
Section: Semen Analysismentioning
confidence: 99%
“…Among them, the software iSperm ® , developed by Aidmics Biotechnology (Taipei City, Taiwan), uses the camera of an iPad Mini 4 (Apple Inc., Cupertino, CA, USA) and a heating chamber to capture and analyze multiple videoframes of semen at 37 °C. The iSperm ® software has species-specific settings and its use in stallions [ 14 , 17 ], boars [ 18 ], and stud dogs [ 19 ] has been reported in the literature. This portable tool was found accurate in estimating different semen concentrations when compared with both NucleoCounter ® and hemocytometer in stallions [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The iSperm ® software has species-specific settings and its use in stallions [ 14 , 17 ], boars [ 18 ], and stud dogs [ 19 ] has been reported in the literature. This portable tool was found accurate in estimating different semen concentrations when compared with both NucleoCounter ® and hemocytometer in stallions [ 14 , 17 ]. Results for motility assessment were encouraging in stallions and dogs [ 14 , 17 , 19 ], although accuracy in estimating velocity parameters should be improved in stallions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%